Frequencies and population densities of plant-parasitic nematodes on banana (Musa AAA) plantations in Ecuador from 2008 to 2014 (2016)
An analysis of the plant-parasitic nematodes found on the banana (Musa AAA) plantations in the provinces of Cañar, El Oro, Guayas, Los Rios and Santo Domingo of Ecuador from 2008 to 2014 was carried out. The nematode extraction was done from 25 g of fresh roots that were macerated in a blender and from which nematodes were recovered in a 0.025 mm (No. 500) mesh sieve. The data were subjected to frequency analysis in PC-SAS and the absolute frequency was calculated for each individual genus. Four plant parasitic nematodes were detected and, based on their frequencies and population densities, the nematode genera in decreasing order was: Radopholus similis Helicotylenchus spp. Meloidogyne spp. Pratylenchus spp. Radopholus similis was the most abundant nematode, accounting for 49 to 66% of the overall root population, followed by Helicotylenchus spp. with 29 to 45% of the population throughout the different analyzed years. From a total of 13,773 root samples, 96% contained R. similis, 91% Helicotylenchus spp., 35% Meloidogyne spp., and 25% Pratylenchus spp. and, when all of the nematodes that were present were pooled (total nematodes), 99.9% of the samples had nematodes. A large number of samples with a nematode population above the economic threshold suggested by Agrocalidad, INIAP and Anemagro (2,500-3,000 nematodes/100 g of roots) was observed in all of the years, the months and the five sampled provinces. The statistical differences (P0.0001) detected for the nematode frequencies among the years, months and provinces, more than likely, were associated with the high number of samples included in each year, month and province because the variations in the frequencies for each nematode genus were small.